Causes of climate change - Malik, Ashok
The increase in the emission of green house gases and the subsequent enhanced greenhouse effect is the root of this problem, and the human activities and processes which cause these are quite comprehensively discussed. Trends in the increase in the concentrations of these green house gases are detailed with the use of tables and graphs, and pie charts have also been included to show the contribution of different gases to global warming.